Hippocampal sclerosis in the parkinsonism‐dementia complex of Guam: quantitative examination of neurons, neurofibrillary tangles, and TDP‐43 immunoreactivity in CA1. Issue 3 (18th March 2015) - Oyanagi, Kiyomitsu; Yamazaki, Mineo; Hashimoto, Tomoyo; Asakawa, Mika; Wakabayashi, Koichi; Takahashi, Hitoshi
<x xml:space="preserve">Abstract</x> The cornu ammonis 1 (CA1) area in the hippocampus of the parkinsonism‐dementia complex (PDC) of Guam was examined quantitatively with special references to the number of neurons, intraneuronal (i) and extracellular (e) neurofibirillary tangles (NFTs), and TDP‐43 (43‐kDa trans‐activation‐responsive region DNA‐binding protein)‐immunopositive structures, in 24 Chamorro patients with PDC of Guam and seven control Chamorro Guamanians (both groups having no ischemic or anoxic complications). The results were that: (i) in the patients with mildly involved PDC, total numbers of neurons, iNFTs and eNFTs were almost the same as those of neurons of controls; (ii) in patients severely involved, total numbers of neurons, iNFTs and eNFTs decreased markedly; (iii) the decrease of the number of pyramidal neurons in CA1 with positive nuclear TDP‐43 was intimately correlated with the decrease in total neuron numbers; (iv) whereas the numbers of neurons and TDP‐43‐immunopositive intracytoplasmic aggregation in the CA1 area were inversely correlated; and (v) depression of nuclear TDP‐43 immuonostainability was not affected by the presence or absence of NFTs. In conclusion, hippocampal sclerosis exists in PDC; there is a possibility of elimination of eNFTs which appeared in the CA1 in patients with PDC and loss of the neurons correlates with disappearance of nuclear TDP‐43, but not with appearance of intraneurocytoplasmic TDP‐43 aggregation or iNFTs.